A multi-treatment two stage allocation design for survival outcomes with nonrandom censoring: a copula-based approach - Das, Soumyadeep; Bhattacharya, Rahul; Shome, Madhumita (Sequential analysis, 2024)
In the context of clinical trials, a multi-treatment two-stage adaptive randomization procedure is developed for survival responses with copula-based nonrandom censoring. Because no such allocation design is available for survival responses with nonrandom censoring, this is probably the first work in this direction. After allocating the first-stage patients by complete randomization (CR), asymptotic p-values of relevant statistical tests are used to derive the allocation probabilities for the second-stage incoming patients. Several design and precision-based operating characteristics of the proposed design are studied both theoretically and empirically and compared with those of the CR procedure and the two-stage design of Bhattacharya and Shome (2019). Applicability of the proposed design is further envisaged through redesigning a real clinical trial with cancer patients.